REMOTE DESKTOP MANAGEMENT IN CLASSROOM - SITAS, Juraj (Trends in education, 2015)
Many vendors offer different software solutions for desktop management in the classroom. This software can facilitate the process of teaching and administration of computers, also in some cases substitute hardware devices such as projector. In this area you can find several applications in commercial software as well as Open Source.
Keywords: management; remote desktop; teaching.